Torakochirurgia Recurrent respiratory infections as an indication for surgery of pulmonary hypoplasia in a 53-year-old patient - Fijołek, Justyna; Wiatr, Elżbieta; Rudziński, Piotr; Orłowski, Tadeusz Maria; Burakowska, Barbara (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Pulmonary hypoplasia is a rare congenital thoracic defect that affects approximately 1–2/12 000 births. This disorder is characterized by presence of a small rudimentary bronchus with pulmonary parenchyma and rudimentary vessels. Many patients with pulmonary hypoplasia die in infancy because of respiratory insufficiency or associated congenital disorders. Some patients survive into adulthood. In this group the main symptoms are: recurrence respiratory infections and dyspnoea. We report a 53-year-old woman in whom pulmonary hypoplasia was diagnosed when she was 43 years old. Surgical treatment was performed 10 years later, because of recurrent respiratory infections and haemoptoe.